Metronidazole Attenuates the Intensity of Inflammation in Experimental Autoimmune Uveitis - Seidler Štangová, Petra; Dušek, Otakar; Klímová, Aneta; Heissigerová, Jarmila; Kučera, Tomáš; Svozílková, Petra (Folia biologica (Praha), 2019)
Autoimmune uveitis is a serious sightthreatening disease that in many cases fails to respond to conventional immunosuppressive or biological therapy. Experimental models used in research allow more detailed study of pathogenesis of the autoimmune process and testing new therapeutic strategies. Recent results show that infection can trigger autoimmune diseases, and some commensal microorganisms are essential in causing disease activity. The aim of this work was to assess the effect of broadspectrum antibiotics - combination of metronidazole and ciprofloxacin or metronidazole alone - on the intensity of intraocular inflammation in experimental autoimmune uveitis (EAU). EAU was induced in mouse strain C57BL/6J by interphotoreceptor retinoid- binding protein in complete Freund's adjuvant and pertussis toxin. The grade of uveitis was assessed clinically and histologically in haematoxylin and eosin- stained tissues. Lymphocytes and macrophages were detected in cryosections using the immunoperoxidase method with antibodies. The therapy was commenced one week before EAU induction and continued throughout the experiment. In addition, metronidazole treatment was also started two weeks before EAU induction. Antibiotics significantly reduced the intensity of uveitis compared to the control group (P < 0.05). The effects of combination of ciprofloxacin and metronidazole and of metronidazole alone were similar when the therapy started one week before EAU induction (P < 0.05). Metronidazole commenced two weeks before EAU induction and throughout the experiment suppressed the intensity of EAU with even higher statistical significance (P < 0.0001). It can be assumed that the high protective effect of metronidazole on EAU intensity may be due not only to its antimicrobial effect, but also to its immunomodulatory activity.
Keywords: stupeň závažnosti nemoci; Animals; Inflammation; ciprofloxacin; zánět; Female; zvířata; uveitida; Mice, Inbred C57BL; Severity of Illness Index; Ciprofloxacin; metronidazol; Metronidazole; ženské pohlaví; Uveitis; myši inbrední C57BL